MENERAPKAN PEDULI STUNTING PADA MASYARAKAT KECAMATAN MONANO - Nova Elysia Ntobuo; Lanto Mohamad Kamil Amali (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
Stunting is an acute nutritional problem which has become an official program of the Government in Presidential Regulation no. 42 of 2013 concerning the National Movement for the Acceleration of Nutrition Improvement. The stunting prevalence rate  in Gorontalo in 2020 was 11.1%, while the comparison of the 2018 Riskesdas results showed that the stunting rate in north gorontalo Regency at the age of 0-24 months was b30, 66% and in the 0-59 month age group was around 33.35%. shows that the number of stunting cases in North Gorontalo is still very high. One part of the community service program is the prevention of stunting that occurs in the community. Because most people do not understand correctly about stunting, and think that stunting or stunted, the term commonly used in society, is a hereditary factor. This community service activity is carried out to increase knowledge and understanding as well as community participation in the stunting prevention and early detection program in toddlers which is expected to directly motivate the community to participate in paying attention to the growth and development of their children so that their growth and development can be optimal. The method used is lecture, interactive, and question and answer.